Concomitant alterations in intragastric pH and ascorbic acid concentration in patients with Helicobacter pylori gastritis and associated iron deficiency anaemia. Issue 4 (1st April 2003) - Annibale, B; Capurso, G; Lahner, E; Passi, S; Ricci, R; Maggio, F; Delle Fave, G
Abstract : Background: Seroepidemiological and clinical studies suggest that Helicobacter pylori may cause iron deficiency anaemia (IDA) in the absence of peptic lesions by undefined mechanisms, which still remain to be fully elucidated. Gastric acidity and ascorbic acid (AA) promote iron absorption. AA is lowered in the presence of H pylori infection. H pylori can cause atrophic body gastritis with achlorhydria, decreased iron absorption, and consequent IDA. Whether alterations in intragastric acidity and AA concentrations play a role in IDA developing in patients with H pylori gastritis remains to be determined . Aim: To evaluate gastric juice pH and gastric juice and plasma AA in patients with H pylori infection and unexplained IDA, compared with controls with IDA and a healthy stomach or with controls with H pylori infection and no IDA. Results: Patients with IDA and H pylori gastritis were characterised by concomitant increased intragastric pH (median value 7) and decreased intragastric AA (median value 4.4 μg/ml) compared with controls with a healthy stomach (median pH 2; median intragastric AA 17.5 μg/ml) and with H pylori positive controls without IDA (median pH 2.1; median intragastric AA 7.06 μg/ml). Intragastric AA was inversely related to pH ( r =−0.40, p=0.0059) and corporal degree of gastritis ( r =−0.53, p=0.0039). Plasma AA concentrations were lower in all infected groups than in healthy controls. Conclusions: Patients with unexplained IDA and H pylori gastritis present concomitant changes in intragastric pH and AA that may justify impaired alimentary iron absorption and consequent IDA.